dogs may be a reservoir host for Angiostrongylus costaricensis - Rubens RODRIGUEZ; Aventino A. AGOSTINI; Sérgio Machado PORTO; Augusto José Oliveira OLIVAES; Susana L. BRANCO; Júlia Pasquali GENRO; Antonio Carlo LAITANO; Rafael Lucyk MAURER; Carlos GRAEFF-TEIXEIRA (Universidade de São Paulo (USP), 2002)
Angiostrongylus costaricensis is a parasitic nematode of wild rodents. Several other vertebrate species including man may become infected by ingestion of the third stage larvae produced by the intermediate hosts, usually slugs from the family Veronicellidae. There is a report of the diagnosis of abdominal angiostrongyliasis in Canis familiaris with lesions resembling those found in human disease. As a preliminar evaluation of the adequacy of a canine model for pathogenetic studies, a dog was inoculated with 75 L3 of A. costaricensis. Infection was established and fist stage larvae were found in feces up to 88 days post infection, sometimes in very large numbers (9.5 x 10(4) L1/g). No clinical manifestations or significant lesions were detected. These are indications that dog may play a role as a reservoir host for A. costaricensis.